Growth, Development, and Water Consumption of Irrigated Bean Crop Related to Growing Degree-Days on Different Soil Tillage Systems in Southeast Brazil - Gerson Araujo de Medeiros; Luiz Antonio Daniel; Felipe Hashimoto Fengler (International Journal of Agronomy)
Degree-days may be an alternative for predicting the influence of temperature on physiological aspects of plants in a changing climate. The objective of this research was to evaluate the relation between cumulative degree-days index (∑G) and the development, growth, and water consumption of irrigated bean under different soil tillage systems (STS). We developed an experiment in Southeast Brazil in plots managed with the following STS: chisel ploughing (CP), disk ploughing (DP), and revolving hoe (RH). The treatments did not influence the crop phenology when correlated to ∑G. The parameters of canopy ground cover, leaf area index, total dry matter, and the plant height presented a highly significant relationship with ∑G (P<0.05). We also compared the results of field water balance with a simulation developed between the crop coefficient and ∑G and found a strong relationship (R2 = 0.93∗∗; ∗∗: high statistical significance (P<0.01)) between these measurements and the model. The total water consumption measured at the irrigated bean crop reached 383 mm, 386 mm, and 375 mm while that simulated from dual crop coefficient approach based on ∑G reached 378 mm, 373 mm, and 349 mm to CP, DP, and RH, respectively, representing a mean difference of 4.2%.